Tourist attractions as a moderating element in explanatory models for loyalty development - Manuel Rey-Moreno; Cayetano Medina-Molina; Ramón Rufín-Moreno (Tourism & Management Studies)
Many studies have analysed the impact of destination image on tourist satisfaction and loyalty, including different mediating variables, both affective and cognitive. This article will attempt to determine whether the representative model of visitors' future behaviour (satisfaction and loyalty) – viewed in terms of destination image, quality, value, disconfirmation, and emotions – follows a common, universal pattern or whether that behaviour actually differs when the model is applied to destinations offering different attractions. The paper below analyses disparate emotional behaviour in relation to destinations mentioned in the literature, when value does not play a mediating role between perception of quality and satisfaction with coastal destinations. This study concludes that there is a common pattern for purely urban cultural destinations while a different pattern exists for urban cultural destinations that include beaches among their attractions.